Disorder in molecular crystals justified with the help of statistical mechanics: a case of two enantiomer solid solutions. Issue 21 (16th May 2019) - Rekis, Toms
Abstract : An elegant statistical mechanics approach has been exploited in combination with accurate quantum chemical calculations to justify the disorder in two previously reported racemic solids. Abstract : An elegant statistical mechanics approach has been exploited in combination with accurate quantum chemical calculations to justify the disorder in two previously reported racemic solids. Generated canonical ensembles and performed lattice energy calculations show that the disorder in the studied systems of small organic enantiomer molecules can be modelled with great accuracy. Ensemble averages fully correspond to the disordered structure models repeatedly obtained in X-ray diffraction studies. The present work not only demonstrates that disorder and its extent in molecular crystals can be theoretically calculated, but also explains from a thermodynamic point of view the origins of the rarely encountered phenomenon of enantiomer solid solutions. Such phases are promising in materials science as their properties can be finely tuned depending on the composition. The lack of complete enantiomer discrimination in the studied examples is evident and it is related to the absence of any donor–acceptor groups providing highly directional interactions, as well as to conformational flexibility in one case and a specific inner symmetry of the molecule in the other one.